2017
DOI: 10.1515/jpem-2016-0310
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis of universal vitamin D supplementation in former East Germany during the first year of life

Abstract: Background: Universal vitamin D supplementation is controversial. Preventative examinations and public health initiatives in former East Germany that included vitamin D prophylaxis for children were regulated by official recommendations and guidelines. The aim of this study is to analyse the impact of a standardised nationwide guideline for universal supplementation with 400 International Units (IU) vitamin D3/day during the first year of life on clinical and biochemical parameters and the influence of surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…It has been observed that 25(OH)D concentrations in infants are lowest in spring, probably due to the low UV levels in winter. Siafarikas et al, in a large ( n = 3481) cross-sectional study of infants under 12 months old, observed that vitamin D concentrations were lowest in March (i.e., after winter in the northern hemisphere) ( p = 0.01) [58]. These findings were corroborated by a large Chinese cross-sectional study [59].…”
Section: Uv Exposure and Seasonal Variationmentioning
confidence: 79%
See 1 more Smart Citation
“…It has been observed that 25(OH)D concentrations in infants are lowest in spring, probably due to the low UV levels in winter. Siafarikas et al, in a large ( n = 3481) cross-sectional study of infants under 12 months old, observed that vitamin D concentrations were lowest in March (i.e., after winter in the northern hemisphere) ( p = 0.01) [58]. These findings were corroborated by a large Chinese cross-sectional study [59].…”
Section: Uv Exposure and Seasonal Variationmentioning
confidence: 79%
“…Modelling has shown that, in the same conditions (season, skin pigmentation, skin exposed, and time spent outdoors), the amount of vitamin D produced by a patient in Darwin (latitude 12° S) is eight times greater than that produced by one in Hobart (latitude 42° S) [60]. The study by Siafarikas et al spanned multiple latitudes in East Germany and found that mean serum 25(OH)D concentrations were higher in the south than in the north (78 nmol/L at 54.1° N, 83 nmol/L at 51.5° N, and 88 nmol/L at 50.6° N) [58].…”
Section: Geographic Factorsmentioning
confidence: 99%
“…Alkaline phosphatase levels (n = 690) were >1500 U/L (95th percentile) in 3.6%. It is conclude that supplementation with 400 IU of vitamin D3 during the first year of life is safe and provides sufficient 25(OH)D levels in an environment of moderate sun exposure as is the case in Germany [17].…”
Section: Vitamin Dmentioning
confidence: 89%
“…Al igual que en otros estudios realizados en niños mayores y adultos, en este estudio se reproduce la variación estacional de los niveles de VD, aumentando en forma clara en el periodo de verano-otoño 24 . Por lo anterior se puede extrapolar que la exposición solar incidiría en lactantes menores aun cuando las recomendaciones son de no exponer.…”
Section: Relación De Niveles De Vitamina D Con Estaciones Del Añounclassified